THE ROLE OF TRAININGS IN THE FORMATION AND DEVELOPMENT OF FUTURE FOREIGN LANGUAGE TEACHERS - Jabbarov, Ulugbek (Журнал иностранных языков и лингвистики, 2020)
THIS ARTICLE IS ABOUT THE ROLE OF TRAININGS IN THE FORMATION AND DEVELOPMENT OF FUTURE FOREIGN LANGUAGE TEACHERS